Tathwiir al-Wasiilat al-Ta’liimiyyat ‘Alaa Asaas al-Tafkiir al-Naqdiy li Thullab Qism Ta’liim al-Lughat al-‘Arabiyyyat Jaami'at Imam Bonjol al-Islamiyyat al-Hukuumiyyat Bi Padang - Khanafi, Zikri; Rahmawati, Rahmawati; Yasmadi, Yasmadi (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
أما أهداف البحث هو لتحليل الاحتياجات المعلم والطلاب في الوسيلة التعليمية التفاعلية ، لتصميم الوسيلة التعليمية التفاعلية على أساس التفكير النقدي لطلاب قـسم تعلـيم اللغة العربية جامعة إمام بونجول الإسلامية الحكومية ببادانج. وأما المدخل في هذا البحث فهو المدخل التطويري. وأما في طريقة البحث التطويري توجد عدد نموذج. والنموذج المستعمل في هذا البحث هو لدي 4د. وطريقة جمع البيانات المستخدمة هي الاستبانة. أما نتيجة البحث فهي أن درجة احتياجات المعلم إلى الوسيلة التعليمية التفاعلية 95 %. واحتياجات الطلاب إلى الوسيلة التعليمية التفاعلية تصل إلى 44،90 %. وأما تصميم الوسيلة التعليمية التفاعلية يتكون على جمع المواد وكتابة المواد على الورق وتحول كتابة المواد إلى الصوت على منصة وصناعة الفيديوا التعليمية على التطبيق Plotagon وكتابة شبكة التدريبات وصناعة التدريبات على منصة Wordwall وتصميم الوسيلة على منصة Padlet. Abstract The research aims to analyze the needs of lecturers and students for interactive learning media, and to design interactive learning media based on higher -order thinking skills for students majoring in Arabic Language Education at Imam Bonjol State Islamic University, Padang. The research method used is research and development. There are several models for development research methods. The model used in this research is 4D. The data collection methods used were questionnaires and were analyzed by statistical calculations. The research results show that the level of teachers' need for interactive education methods is 95%. Students' need for interactive educational facilities reached 90.44%. The process of designing interactive learning media includes collecting teaching materials collected from semester learning plans, writing learning materials in Word, converting written teaching materials into sound using the platform text-to-speech platform, making videos of learning materials using the Plotagon application, makcreating exercises to measure student abilities using the platform Wordwall, and designing interactive learning media on the Padlet platform.